Escaping the climate policy uncertainty trap: options contracts for REDD+. (26th November 2018) - Golub, Alexander A.; Fuss, Sabine; Lubowski, Ruben; Hiller, Jake; Khabarov, Nikolay; Koch, Nicolas; Krasovskii, Andrey; Kraxner, Florian; Laing, Timothy; Obersteiner, Michael; Palmer, Charles; Piris-Cabezas, Pedro; et al.
ABSTRACT: Climate policy uncertainty significantly hinders investments in low-carbon technologies, and the global community is behind schedule to curb carbon emissions. Strong actions will be necessary to limit the increase in global temperatures, and continued delays create risks of escalating climate change damages and future policy costs. These risks are system-wide, long-term and large-scale and thus hard to diversify across firms. Because of its unique scale, cost structure and near-term availability, Reducing Emissions from Deforestation and forest Degradation in developing countries (REDD+) has significant potential to help manage climate policy risks and facilitate the transition to lower greenhouse gas emissions. 'Call' options contracts in the form of the right but not the obligation to buy high-quality emissions reduction credits from jurisdictional REDD+ programmes at a predetermined price per ton of CO2 could help unlock this potential despite the current lack of carbon markets that accept REDD+ for compliance. This approach could provide a globally important cost-containment mechanism and insurance for firms against higher future carbon prices, while channelling finance to avoid deforestation until policy uncertainties decline and carbon markets scale up. Key policy insights Climate policy uncertainty discourages abatement investments, exposing firms to an escalating systemic risk of future rapid increases in emission control expenditures. This situation poses a risk of an abatement 'short squeeze, ' paralleling the case in financial markets when prices jump sharply as investors rush to square accounts on an investment they have sold 'short', one they have bet against and promised to repay later in anticipation of falling prices. There is likely to be a willingness to pay for mechanisms that hedge the risks of abruptly rising carbon prices, in particular for 'call' options, the right but not the obligation to buy high-quality emissions reduction credits at a predetermined price, due to the significantly lower upfront capital expenditure compared to other hedging alternatives. Establishing rules as soon as possible for compliance market acceptance of high-quality emissions reductions credits from REDD+ would facilitate REDD+ transactions, including via options-based contracts, which could help fill the gap of uncertain climate policies in the short and medium term.